STUDI PENERAPAN GOOD GOVERNANCE DALAM PENGELOLAAN DESA WISATA KAMPUNG BANDAR KECAMATAN SENAPELAN KOTA PEKANBARU TAHUN 2012-2014 - Erlina Ayu Ningrum; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aimed to determine the application of good governance in the management of tourism in the city of Pekanbaru. This study focused on the management of tourism in the district Senapelan called Kampung Bandar Tourism Village. Management of Tourism Village Kampung Bandar not quite optimal, high demand for tourism is not comparable with the services provided by the government will be the satisfaction of tourism. With the formulation of research problems that How the application of good governance in the management of tourism village Kampung Bandar and the factors that affect not optimal implementation of good governance. Based on the above background, the study aims to identify and analyze the implementation of good governance in the management of Kampung Bandar Tourism Village in the city of Pekanbaru. The research method is qualitative descriptive type of research that data collection is by interview, documentation and observation. From the results of the field studies showed in the management of tourism village government has not been optimal in applying the principles of good governance, it is visible from the lack of involvement of all components of society, government and private. Six principles of good governance which is used by penulis.Keenam these principles have not been fully implemented seraca maximum. In the principle of community participation sufficiently participate in the management of rural tourism, in this case the government has not been transparent menganai developer programs tourist village. The government's response also still lemah.Program Tourism Village is still not sufficiently effective and efficient. The factors that affect not optimal implementation of good governance in the management of rural tourism is a factor of a government that has not been able to implement a culture of good governance and weak in responding to the demands of the people. In this study the authors conclude that good governance is not optimal in the management of tourism village Kampung Bandar. But the government should put more effort to manage tourism along with public and private sector, especially the tourism village Kampung Bandar Senapelan Pekanbaru. Keywords: Good Govenance, Tourism Village